The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1002/oms.1210290908
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of collisionally activated hydroxyphenoxide anions in the gas phase

Abstract: Low-energy collisionally activated dissociation of 0-deprotonated dihydroxybenzenes (catechol, resorcinol, hydroquinone) in the gas phase causes both fragmentation to form IC,H,O,J-ions by loss of the remaining oxygen-bound hydrogen atom and intramolecular hydrogen atom migration from 0 to C. The rearranged anions then undergo ring-cleavage reactions which are different in each case. Both catechol and hydroquinone produce fragments which are the result of the loss of two carbon atoms and both oxygen atoms but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The cleavage of H 2 O frequently represents the occurrence of an aliphatic hydroxyl moiety and less often of an aromatic alcohol moiety. 18,28 Since a cleavage of H 2 O is not observed in the MS 2 spectrum of BP-4, an aromatic hydroxyl group can be ruled out as origin. On the basis of MS 3 fragmentation, the benzhydrol derivative of BP-4 can be suggested to be TP 310.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The cleavage of H 2 O frequently represents the occurrence of an aliphatic hydroxyl moiety and less often of an aromatic alcohol moiety. 18,28 Since a cleavage of H 2 O is not observed in the MS 2 spectrum of BP-4, an aromatic hydroxyl group can be ruled out as origin. On the basis of MS 3 fragmentation, the benzhydrol derivative of BP-4 can be suggested to be TP 310.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Structures such as hydroxylated cyclic and polycyclic structures (i.e., polyphenols) are also prone to multiple gas phase artifacts, including water elimination (loss À17), hydrogen elimination (À1), radical fragmentation (loss À15, À14), Retro-Diels-Alder (RDA) reactions (C-ring electron rearrangement) (þ or À2), gas-phase dimers, or combinations thereof (such as loss À13 or À12). [56][57][58] Finally, in-source fragmentation following soft-ionization is often observed for sugars and phase II conjugates, particularly sulfate and glucuronide conjugates.…”
Section: Qualitative Accuracymentioning
confidence: 99%
“…One theoretical study found a calculated barrier of approximately 2360 cm –1 for intramolecular transfer of the proton between the two O atoms in o -HPO – , sufficiently large to make proton tunneling negligible. Experimental work has studied collision-induced fragmentation of o -HPO – and the kinetics of its reactions with BF 3 and SiF 4 . A study by Fattahi et al estimated the electron binding energy and proton affinity of o -HPO – through bracketing with numerous ion–molecule reactions.…”
Section: Introductionmentioning
confidence: 99%